IEO Evaluation Report : IMF Forecasts. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2014)
The Independent Evaluation Office (IEO) was established by the IMF's Executive Board in 2001. It provides objective and independent evaluation of issues related to the IMF. The IEO operates independently of IMF management and at arm's length from the IMF Executive Board. For more information on the IEO's activities, visit the IEO website: www.ieo-imf.org.